High proportion of adults with type 2 diabetes and poor glycated hemoglobin perceived that their diabetes control was excellent - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Loh, Huai Heng (Professional Section of Diabetes Canada, 2019)
Objectives As is true for other chronic illnesses, perception of disease control is pivotal to patient empowerment in diabetes care. This study aimed to describe the perception of diabetes control by patients with poor glycated hemoglobin (A1C) levels so as to explore the relationship between perception and various sociodemographic and disease characteristics and to measure the patients' knowledge, attitudes and practices in diabetes care.